Call me Maria : a novel - Cofer, Judith Ortiz, 1952- (New York : Scholastic Inc, 2006)
Fifteen-year-old Maria leaves her mother and their Puerto Rican home to live in the barrio of New York with her father, feeling torn between the two cultures in which she has been raised.
G8
Keywords: Puerto Ricans -- New York (State) -- New York -- Juvenile fiction; Puerto Ricans -- New York (State) -- New York -- Fiction; Identity -- Fiction; New York (N.Y.) -- Fiction